2015
DOI: 10.1097/md.0000000000001137
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Characterization of Cytokine Responses to Enterovirus 71 and Coxsackievirus A16 Infection in Children

Abstract: Viral encephalitis is a serious complication of hand, foot, and mouth disease (HFMD), but characteristics of cytokines response in enterovirus 71 (EV-71) and/or coxsackievirus A16 (CV-A16) associated HFMD with or without viral encephalitis remained unclear.We performed a multigroup retrospective study and compared the serum cytokines concentrations among 16 encephalitis patients infected with EV-71 and CV-A16, 24 encephalitis patients with single EV-71 infection, 34 mild HFMD patients with EV-71 infection, 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
3
12
2
3
Order By: Relevance
“…In the current study, significant differences in plasma levels of IL-22 were observed among HC and, mild and severe patients, which suggested that elevated levels of IL-22 cytokines might play an important role in the pathogenesis of EV71-associated HFMD, which was consistent with previous reports [29]. Subsequent correlation analysis of plasma levels of IL-22 and the frequencies of cTh22 cells further indicated that increased IL-22 levels might be predominantly secreted by cTh22 cells in the patients with EV71-associated HFMD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, significant differences in plasma levels of IL-22 were observed among HC and, mild and severe patients, which suggested that elevated levels of IL-22 cytokines might play an important role in the pathogenesis of EV71-associated HFMD, which was consistent with previous reports [29]. Subsequent correlation analysis of plasma levels of IL-22 and the frequencies of cTh22 cells further indicated that increased IL-22 levels might be predominantly secreted by cTh22 cells in the patients with EV71-associated HFMD.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, correlation analysis showed an increase in the plasma levels of IL-17A and the frequencies of cTh17 cells, which also implied that the increased IL-17A expressions might be predominantly produced by cTh17 cells and associated with the pathogenesis of EV71-associated HFMD. Moreover, plasma levels of TNF-α, IL-6 and IL-23 cytokines were significantly higher in the EV71-associated HFMD patients than in HC, particularly in the severe patients, which was consistent with previous reports [4, 29, 30]. These findings indicated that increased plasma levels of cytokines (TNF-α, IL-6 and IL-23) possibly could explain the increased percentages of cTh22 and cTh17 cells and plasma levels of IL-22 and IL-17A in patients with EV71-associated HFMD, particularly in the severe patients.…”
Section: Discussionsupporting
confidence: 92%
“…The levels of IL-4 among the cases were significantly different and increased from the 2nd day to the 4th day (p < 0:001), especially in the fatal cases accompanied with brainstem encephalitis, neurogenic pulmonary edema, and sepsis [10]. On the other hand, serum levels of IL-4 were significantly higher in the EV71-infected encephalitis patients than those in the HFMD-alone patients when adjusting for age and sex [29]. In this way, it is strongly believed that EV71 infection is associated with higher risk of encephalitis development.…”
Section: Il-2 Familymentioning
confidence: 92%
“…IL-4 is mainly produced by Th2 cells, mast cells, and basophils, which can promote the proliferation and differentiation of B cells, induce IgG1 and IgE production, facilitate Th0 cells to differentiate into Th2 cells, and so on [28]. The dynamic changes of the IL-4 with the progression of HFMD and its severity have been studied [10,22,29]. The levels of IL-4 among the cases were significantly different and increased from the 2nd day to the 4th day (p < 0:001), especially in the fatal cases accompanied with brainstem encephalitis, neurogenic pulmonary edema, and sepsis [10].…”
Section: Il-2 Familymentioning
confidence: 99%
“…Zhang and colleagues also showed that HFMD cases with clinical meningoencephalitis caused by viral infection (enterovirus and coxsackie virus) showed higher levels of IL-1β than those without meningoencephalitis [13]. A previous study demonstrated that bacterial meningoencephalitis (meningococcus or pneumococcus) caused an elevation of IL-1β [8].…”
Section: Resultsmentioning
confidence: 97%